341 ROLE AND TOLERANCE OF LUMBAR PUNCTURE TESTS FOR CSF BIOMARKERS OF ALZHEIMER'S DEMENTIA IN A SPECIALIZED MEMORY CLINIC. (25th October 2022) - Clancy, C; Dolphin, H; McHale, C; Dookhy, J; Fallon, A; Kennelly, S
Abstract: Background: People living with mild cognitive symptoms often require clarity on the underlying aetiology of their symptoms, and with the advent of disease modifying therapies for Alzheimer's Disease (AD), establishing diagnostic accuracy for amyloid and tau pathology in AD will become more clinically relevant. CSF biomarker analysis via Lumbar Puncture (LP) is the most accurate and cost-effective means of establishing AD pathology. This study aimed to assess memory clinic patients' tolerance of LP as a diagnostic tool in the work-up of memory symptoms. Methods: A consecutive sample of patients offered CSF analysis as part of their diagnostic plan in a tertiary memory service of a University Teaching Hospital were included. After clinician discussion, an LP for AD biomarker detection is offered to all patients with amnestic/non-amnestic mild cognitive impairment, or those with atypical motor-cognitive symptoms in this service. Results: 119 patients offered an LP from 2019-2020 were contacted, fifty-four (45%) of whom participated in this study. The average age was 70.1 (±7.5) years, 50% female. Forty-two (42/54, 78%) had an LP performed. More women declined an LP than men (8/12, 66%). Almost all of those who had an LP, (38/42, 90.4%) thought it yielded useful information and would recommend it for others. Side effects included mild back pain relieved with simple analgesia (11/42, 26%) and headache (3/42, 7%). There were no incidences of neurological sequelae or requirements for dural patch. Of the 12/54 (22%) who declined CSF analysis; reasons for same were pre-existing back pain (3/12, 25%), needle-phobia (3/12, 25%), and only 2/12, (16%) declined because they did not wish to know the results of the investigation. Conclusion: This study highlights high levels of acceptance of CSF analysis when offered as part of routine care, with infrequent side effects. Most patients found the clinical information yielded was useful.